Accounting Information System Analysis of Goods Delivery Expeditions at PT. Eka Sari Lorena - Sitohang, Rommel; Sipayung, Tri Dharma (PT FORMOSA CENDEKIA GLOBAL, 2024)
PT. Eka Sari Lorena (PT ESL) is a service company engaged in the delivery of goods or packages. The accounting information system is an important part of the goods delivery process for the company. The purpose of this article is to analyze PT ESL's goods delivery accounting information system. This research is descriptive qualitative in nature. Data collection was carried out through interviews and observations with related parties to find out directly about the practices of PT ESL's goods delivery accounting information system. From the results of the analysis it can be concluded that PT ESL's goods delivery travel accounting information system is still not effective and functional. The first is that the number of goods sent has fluctuated in recent years, and the second is that there are constant errors when sending goods so that the target for sending goods is not achieved